[AU(DIEN)Cl]Cl2: Exchange Phenomena Observed by H1 and C13 NMR Spectroscopy. Issue 4 (1999) - Best Best, Sabine L. Sabine L.; Guo Guo, Zijian Zijian; Djuran Djuran, Milos I. Milos I.; Sadler Sadler, Peter J. Peter J.
Abstract : The solution behaviour of the square-planar gold(III) complex [Au(dien)Cl]Cl 2 (dien = 1, 5- diamino-3-azapentane) was investigated by H 1 and C 13 NMR spectroscopy. We have found that H 1 NMR spectra of [Au(dien)Cl]Cl 2 are characterised by exchange behaviour over the whole pH range, and some exchange effects are also seen in C 13 NMR spectra of the deprotonated hydroxo derivative of the complex in alkaline solution. An exchange rate of > 378 s -1 was determined from H 1 NMR spectra at pH ∗ 2 (coalescence temperature 40 C ° ). In slightly acidic solutions of the complex, H 1 chemical shifts are in accordance with the known deprotonation of the central amine group of the complexed diethylenetriamine ligand. In C 13 NMR spectra, two separate sets of resonances are observed for the chloro and the hydroxo complex of gold(III) diethylenetriamine. The hydroxo complex [ Au ( dien-H ) OH ] + shows exchange effects in C 13 NMR spectra. Variable temperature studies show the carbon atoms next to the central secondary amine to be inequivalent and each present in two different environments that are in intermediate to fast exchange on the NMR time-scale.